RELATIONS AND ORGANIZATIONAL FORMS OF ACTIVE CITIZENSHIP - D’Ambrosi, Lucia (European Scientific Journal, ESJ, 2014)
The modalities that active citizenship finds to act (in social, environmental, cultural contexts, etc.), developed in the last few years in Europe, with or without the institutional support, have represented an important resource for the growth and safeguard of common goods. The territory is the place where individual and community’s needs and rights emerge and they can only be satisfied when citizens participate to public life adopting new modalities. However, active citizenship does not always acquire those features that make it formally recognized as an association with a specific role within the public area. Sometimes, it rather appears as an extemporary mobilization that fades away as soon as the strong call becomes weaker; sometimes, also, it happens to pursue different purposes related to specific pressing urges. This paper will analyze the various forms of active citizenship (from voluntary associations to civic organizations up to defining real collective mobilizations), examining its modalities of intervention and the level of involvement in public policies. Such forms of activism open interesting questions for a survey concerning the capability that citizens have in creating social capitals and in cooperating for the safeguard of the general interest.